Regulating netflix: a comparative study of Malaysia and Singapore - Islam, Md. Zahidul (2020)
The purpose of this study is to analyse the existing legal and regulatory framework of Malaysia and Singapore governing Netflix services with a view to identify the loopholes and to recommend some solutions. This study uses a legal and doctrinal research methodology followed by an analytical approach. In identifying and interpreting data both primary and secondary legal sources were considered. Findings of this study revealed that Netflix in Malaysia and Singapore are governed by the laws that regulate traditional broadcasting services. This study denotes the legal and regulatory context governing Netflix in Malaysia and Singapore. In conclusion, it is recommended that both the countries need to enact specific legal regime to regulate and control over-the-top (OTT) broadcasting services like Netflix.